Flux-cored wire for gas shielded arc welding

JP7638593B2Active Publication Date: 2025-03-04NIPPON STEEL WELDING & ENGINEERING CO LTD
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
JP2021050622
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-24
Publication Date
2025-03-04
Estimated Expiration
2041-03-24

AI Technical Summary

Benefits of technology

【0018】 本発明のガスシールドアーク溶接用フラックス入りワイヤによれば、溶接入熱量20kJ/cm程度の低入熱の溶接条件から溶接入熱量60kJ/cmの大入熱で高パス間温度のような高能率の溶接施工条件で溶接をしても、溶接欠陥が生じることなく良好な機械的性質を有する溶接金属を得ることができ、高電流の溶接でもアークが安定してスパッタ発生量が少なく、ビード外観·形状が良好であるなどの溶接作業性に優れる等、高品質な溶接部を高能率に得ることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007638593000001
    Figure 0007638593000001
  • Figure 0007638593000002
    Figure 0007638593000002
  • Figure 0007638593000003
    Figure 0007638593000003
Patent Text Reader

Abstract

To provide a flux-cored wire for gas-shielded arc welding that gives a weld metal having good mechanical properties, generates stable arc, and is excellent in welding workability even when welding is performed under low heat input welding conditions and high-efficiency welding conditions such as high heat input and high interpass temperature.SOLUTION: A flux-cored wire for gas-shielded arc welding in which a steel outer skin is filled with flux, contains C: 0.04 to 0.10%, Si: 0.4 to 1.4%, Mn: 1.7 to less than 2.5%, Mo: 0.6 to 1.0%, Cu: 0.05 to 0.5%, Ti: 0.1 to 0.4%, and B: 0.0015 to 0.010% in mass % in terms of the total mass of the wire in the total of the steel outer skin and the flux, and further contains a total F conversion value: 0.005 to 0.10%, a total SiO2 conversion value: 0.01 to 0.2%, and a total of Na2O conversion value and K2O conversion value: 0.02 to 0.14% in mass % in terms of the total mass of the wire in the flux.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a flux-cored wire for gas-shielded arc welding, which can produce weld metal with good mechanical properties even when welding under low heat input conditions to high-efficiency welding conditions of high heat input and high interpass temperature, and which has a stable arc even when welding with a high current, with little spatter generation and excellent welding workability. [Background technology]

[0002] In the fields of shipbuilding and steel building, gas-shielded arc welding using solid wires is widely used as a highly efficient welding method for steel structures. The welding conditions applied are high current and high heat input of 30 to 40 kJ / cm. Furthermore, if the time of each welding pass is shortened and welding is performed as continuously as possible, the interpass temperature becomes high. In recent years, in order to further improve welding efficiency, welding with a high heat input and high interpass temperature of more than 40 kJ / cm is being shifted to, but the weld metal needs to have a certain strength and toughness. However, when welding with such a high heat input and high interpass temperature, the mechanical properties of the weld metal tend to deteriorate, making it difficult to obtain a sound welded joint, and there are problems in that a lot of large spatter is generated when welding with a high current using a solid wire for gas-shielded arc welding, and welding workability is significantly deteriorated.

[0003] As a means for solving these problems, several Ti-B based welding materials have been proposed as welding solid wires that can obtain weld metals with excellent mechanical properties in welding with large heat input and high interpass temperatures. For example, Patent Document 1 proposes a welding solid wire that contains one or more of C, Si, Mn, Ti, and Mg or Al, and also contains predetermined amounts of B, Cu, Ni, Cr, and Mo.

[0004] Also, Patent Document 2 proposes a welding solid wire that contains C, Si, Mn, Ti, Al, Cu, Mo, and B, further contains a predetermined amount of Ni, limits N to a certain amount or less, and further contains a predetermined amount of K. However, the welding solid wires disclosed in Patent Documents 1 and 2 can obtain excellent properties in strength and toughness of the weld metal when welded under high heat input and high interpass welding conditions with a welding heat input of up to 40 kJ / cm, but cannot satisfy predetermined mechanical properties, such as excessive strength of the weld metal, under low heat input welding conditions with a welding heat input of about 20 kJ / cm, such as horizontal position welding.

[0005] Patent Document 3 discloses a welding solid wire containing appropriate amounts of C, Si, Mn, Mo, Ti, B, Cu, Ni, and Cr, which allows the strength and toughness of the weld metal to be obtained even when welding is performed with low to high heat input and high interpass temperature. However, even with the welding solid wire disclosed in Patent Document 3, there is a problem that the strength and toughness of the weld metal cannot be obtained under welding conditions of high heat input exceeding 40 kJ / cm and high interpass temperature, and the amount of spatter generated during welding is large.

[0006] Solid wires for gas shielded arc welding that generate less spatter, a problem that occurs when welding with a high current, have been developed. For example, Patent Document 4 discloses a technology that contains rare earth elements, has a solid lubricant on the wire surface, and further has a liquid lubricant coating on the outer peripheral surface of the solid lubricant, thereby reducing the amount of spatter and improving wire feedability.

[0007] Patent Document 5 discloses a solid wire for gas-shielded arc welding that can reduce the amount of spatter by forming an alkali-metal-impregnated portion impregnated with two or more types of alkali metals under the wire surface. However, in high-current welding using a solid wire for gas-shielded arc welding, a large amount of spatter is generated, so that even if the wire feedability is improved, the amount of spatter cannot be sufficiently reduced, and the bead appearance and shape cannot be improved.

[0008] On the other hand, as a flux-cored wire for gas-shielded arc welding that ensures the strength and toughness of the weld metal under welding conditions of high heat input and high interpass temperature and has good welding workability, for example, Patent Documents 6 and 7 disclose flux-cored wires that provide good welding workability under welding conditions of high heat input and high interpass temperature and that provide weld metal with excellent mechanical properties. However, even these flux-cored wires have a problem in that the strength and toughness of the weld metal cannot be obtained under welding conditions of high heat input and high interpass temperature where the welding heat input exceeds 40 kJ / cm. In addition, the latter also generates a large amount of slag, which causes a problem in that welding defects such as slag inclusion are more likely to occur. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] JP 2008-142726 A [Patent Document 2] JP 2004-237361 A [Patent Document 3] JP 2003-136281 A [Patent Document 4] JP 2005-169415 A [Patent Document 5] JP 2009-255142 A [Patent Document 6] JP 2005-279683 A [Patent Document 7] JP 2015-205303 A Summary of the Invention [Problem to be solved by the invention]

[0010] The present invention has been devised in consideration of the above-mentioned problems, and has an object to provide a flux-cored wire for gas-shielded arc welding which is capable of producing a weld metal having good mechanical properties without causing welding defects even when welding is performed under welding conditions ranging from a low heat input of about 20 kJ / cm to a high heat input of 60 kJ / cm and a high interpass temperature, and which has a stable arc even when welding with a high current, with little spatter generation and excellent welding workability. [Means for solving the problem]

[0011] The present inventors have conducted detailed studies on the component composition of a flux-cored wire for gas-shielded arc welding, which is capable of producing a weld metal having good mechanical properties without causing welding defects even when welding is performed under welding conditions ranging from a low heat input of about 20 kJ / cm to a high heat input of 60 kJ / cm and a high interpass temperature, and which has excellent welding workability, such as a stable arc and little spatter even when welding with a high current.

[0012] As a result, it was found that in order to achieve appropriate strength and stable toughness of the weld metal without the occurrence of welding defects even under low heat input welding conditions of about 20 kJ / cm, high current welding conditions, and high heat input and high interpass temperature welding conditions of 60 kJ / cm, it is effective to minimize the oxides, which are slag forming agents in the wire, and to optimize the amounts of each of the alloy components C, Si, Mn, Cu, and Ti.

[0013] In addition, it was discovered that by adjusting the amounts of Mo and B in the wire to appropriate levels, it is possible to obtain weld metal with a specified tensile strength without reducing the toughness of the weld metal, even under welding conditions with a large heat input of 60 kJ / cm and a high interpass temperature.

[0014] Furthermore, it was also found that the toughness of the weld metal can be further improved by adjusting the amounts of Al and Mg in the wire to appropriate levels.

[0015] In addition, it was found that, in terms of welding workability, the total of the F-equivalent values ​​of C, Ti, and metal fluorides, and the total of the Na2O-equivalent values ​​and K2O-equivalent values ​​of Na oxides and K oxides can be set to appropriate amounts to stabilize the arc and reduce the amount of spatter generated, and that the appearance and shape of the bead can be improved by setting the total of the SiO2-equivalent values ​​of Si oxides to an appropriate amount.

[0016] That is, the gist of the present invention is a flux-cored wire for gas shielded arc welding, which is made by filling a steel sheath with flux, the total of the steel sheath and the flux containing, in mass % relative to the total mass of the wire, 0.04 to 0.10% C, 0.4 to 1.4% Si, 1.7 to less than 2.5% Mn, 0.6 to 1.0% Mo, 0.05 to 0.5% Cu, 0.1 to 0.4% Ti, and 0.0015 to 0.010% B, The flux contains, in mass % relative to the total mass of the wire, metal fluorides: 0.005 to 0.10% in F conversion, silicon oxides: 0.01 to 0.2% in SiO2 conversion, one or more of sodium oxides and potassium oxides: 0.02 to 0.14% in Na2O conversion and K2O conversion, with the remainder being Fe from the steel sheath, iron powder added to adjust the composition, the Fe content of the iron alloy powder, and unavoidable impurities.

[0017] The flux-cored wire for gas-shielded arc welding further contains, in mass % relative to the total mass of the wire, 0.25% or less of either or both of Al and Mg in total, based on the total mass of the steel sheath and flux. Effect of the Invention

[0018] According to the flux-cored wire for gas shielded arc welding of the present invention, even when welding is performed under welding conditions ranging from a low heat input of about 20 kJ / cm to a high heat input of 60 kJ / cm and a high interpass temperature, it is possible to obtain a weld metal having good mechanical properties without generating weld defects, and even when welding with a high current, the arc is stable, the amount of spatter is small, and the bead appearance and shape are good, resulting in excellent welding workability, and thus a high-quality weld can be obtained with high efficiency. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] The composition and content of the flux-cored wire for gas shielded arc welding according to the present invention, and the reasons for limiting each component will be described below. The content of each component is expressed in mass%, and the mass% is simply expressed as %.

[0020] [Total of steel sheath and flux: C: 0.04~0.10%] C has the effect of improving the strength of the weld metal. If C is less than 0.04%, sufficient weld metal strength cannot be obtained under welding conditions of large heat input and high interpass temperature. On the other hand, if C exceeds 0.10%, the strength of the weld metal increases but the toughness decreases. Therefore, the total C content of the steel sheath and flux is set to 0.04 to 0.10%. Note that C can be added from the components contained in the steel sheath, as well as from the flux, metal powder, alloy powder, etc.

[0021] [Si: 0.4~1.4% in total for steel sheath and flux] Silicon is a deoxidizing agent and adjusts the amount of oxygen in the weld metal. Silicon also has the effect of improving the strength of the weld metal. If the amount of silicon is less than 0.4%, the deoxidization is insufficient, the strength of the weld metal is low, and the toughness is reduced. On the other hand, if the amount of silicon exceeds 1.4%, the strength of the weld metal becomes excessively high, and the toughness cannot be obtained stably. If the amount of silicon exceeds 1.4%, the amount of slag generated during welding increases, and welding defects such as slag inclusion are likely to occur. Therefore, the total amount of silicon in the steel sheath and the flux is set to 0.4 to 1.4%. In addition to the components contained in the steel sheath, silicon can be added from the flux as metal silicon, Fe-Si, Fe-Si-Mn, and other alloy powders.

[0022] [Mn: less than 1.7-2.5% in total for steel sheath and flux] Mn has the effect of improving the toughness and strength of the weld metal under welding conditions of high heat input and high interpass temperature. If Mn is less than 1.7%, the strength of the weld metal decreases under welding conditions of high heat input and high interpass temperature, and the toughness decreases. On the other hand, if Mn is 2.5% or more, the strength of the weld metal increases with low heat input welding, and toughness cannot be obtained stably. In addition, if Mn is 2.5% or more, the amount of slag increases under both low heat input and high heat input and high interpass temperature welding conditions, and welding defects such as slag inclusion become more likely to occur. Therefore, the total Mn content of the steel sheath and flux should be less than 1.7 to 2.5%. In addition to the components contained in the steel sheath, Mn can be added from alloy powders such as metal Mn, Fe-Mn, and Fe-Si-Mn.

[0023] [Mo: 0.6~1.0% in total for steel sheath and flux] Mo is important for ensuring the strength of the weld metal under welding conditions of high heat input and high interpass temperature when Mn is within the above-mentioned range. If Mo is less than 0.6%, the strength of the weld metal will be low under welding conditions of high heat input and high interpass temperature. On the other hand, if Mo exceeds 1.0%, the strength of the weld metal will be excessively high under welding conditions of low heat input, and toughness will not be stably obtained. Therefore, the total Mo content of the steel sheath and flux should be 0.6 to 1.0%. Note that Mo can be added from metallic Mo powder from the flux, in addition to the components contained in the steel sheath.

[0024] [Cu: 0.05~0.5% in total for steel sheath and flux] Cu has a precipitation strengthening effect, lowers the transformation temperature, refines the structure of the weld metal, and stabilizes the toughness. If Cu is less than 0.05%, this effect cannot be obtained, and stable toughness of the weld metal cannot be obtained. On the other hand, if Cu exceeds 0.5%, precipitation embrittlement occurs, the toughness of the weld metal decreases, and hot cracking becomes more likely to occur. Therefore, the total Cu content of the steel sheath and flux is set to 0.05 to 0.5%. Cu can be added from the components contained in the steel sheath and the Cu plating applied to the surface of the steel sheath, as well as from metallic Cu from the flux and alloy powder such as Fe-Si-Cu.

[0025] [Ti: 0.1-0.4% in total for steel sheath and flux] Ti stabilizes the arc, especially during high current welding and high heat input / high interpass temperature welding, and acts as a deoxidizer, while also generating fine Ti oxides in the weld metal, which improves the toughness of the weld metal. If Ti is less than 0.1%, this effect cannot be obtained, and the arc becomes unstable and the toughness of the weld metal decreases during high current welding and high heat input / high interpass temperature welding. On the other hand, if Ti exceeds 0.4%, Ti precipitates increase in the weld metal, which reduces the toughness. Therefore, the total Ti content of the steel sheath and flux is 0.1 to 0.4%. In addition to the components contained in the steel sheath, Ti can be added from metallic Ti from the flux, alloy powder such as Fe-Ti, etc.

[0026] [Total of steel sheath and flux: B: 0.0015~0.010%] B has the effect of suppressing the formation of grain boundary ferrite at the grain boundaries of the weld metal and improving toughness under welding conditions of large heat input and high interpass temperature. If B is less than 0.0015%, the toughness of the weld metal decreases under welding conditions of large heat input and high interpass temperature. On the other hand, if B exceeds 0.010%, hot cracking is likely to occur. Therefore, the total B content of the steel sheath and flux is 0.0015 to 0.010%. Note that B can be added from alloy powders such as Fe-Si-B and Fe-Mn-B, in addition to the components contained in the steel sheath.

[0027] [Metal fluorides in flux: Total F conversion value: 0.005~0.10%] Metal fluorides have the effect of concentrating and stabilizing the arc. If the total F-equivalent value of the metal fluorides is less than 0.005%, this effect is not obtained, the arc becomes unstable, and the amount of spatter generation increases. On the other hand, if the total F-equivalent value of the metal fluorides exceeds 0.10%, the arc becomes strong and unstable, and the amount of spatter generation increases. Therefore, the total F-equivalent value of the metal fluorides contained in the flux is 0.005 to 0.10%. Note that the metal fluorides can be added from CaF2, NaF, LiF, MgF2, K2SiF6, Na3AlF6, AlF3, etc. from the flux, and the F-equivalent value is the total amount of F contained therein.

[0028] [Si oxide in flux: Total of SiO2 equivalent: 0.01-0.2%] The silicon oxide in the flux has the effect of increasing the viscosity of the molten slag, improving the slag encapsulation, improving the conformity of the bead toe, and improving the bead appearance and shape. If the total of the silicon oxides in terms of SiO2 is less than 0.01%, the conformity of the weld bead toe will be poor, and the bead appearance and shape will be poor. On the other hand, if the total of the silicon oxides in terms of SiO2 exceeds 0.2%, the amount of oxygen in the weld metal will increase and the toughness will decrease. Also, if the total of the silicon oxides in terms of SiO2 exceeds 0.2%, the amount of slag will increase, and welding defects such as slag inclusion will easily occur. Therefore, the total of the silicon oxides in terms of SiO2 contained in the flux should be 0.01 to 0.2%. The silicon oxide can be added from the solid components of water glass made of silica sand, orthoclase, and potassium silicate from the flux.

[0029] [One or more of Na oxide and K oxide in the flux: 0.02 to 0.14% in total in Na2O and K2O equivalents] Na oxide and K oxide have the effect of stabilizing the arc. If the total of one or more of Na oxide and K oxide is less than 0.02% in terms of Na2O and K2O, the arc becomes unstable and the amount of spatter increases. On the other hand, if the total of one or more of Na oxide and K oxide exceeds 0.14% in terms of Na2O and K2O, the arc becomes unstable and the amount of spatter increases. If the total of one or more of Na oxide and K oxide exceeds 0.14% in terms of Na2O and K2O, the amount of slag generated during welding increases, and welding defects such as slag inclusion tend to occur. Therefore, the total of one or more of Na oxide and K oxide contained in the flux is 0.02 to 0.14% in terms of Na2O and K2O. Na oxide and K oxide can be added from powders such as solid components of water glass made of sodium silicate and potassium silicate, potassium feldspar, sodium titanate, etc.

[0030] [Al and / or Mg in the steel sheath and flux combined: 0.25% or less] Al and Mg are strong deoxidizers that reduce oxygen in the weld metal and increase the toughness of the weld metal. However, if either or both of Al and Mg exceed 0.25%, a strong oxidation reaction occurs in the arc during welding, resulting in an increase in the amount of fume and spatter generated. Therefore, the total content of either or both of Al and Mg in the steel sheath and flux should be 0.25% or less. In order to reduce oxygen in the weld metal and increase the toughness of the weld metal, it is preferable that either or both of Al and Mg be 0.05% or more. Al and Mg can be added from alloy powders such as metallic Al, Fe-Al, metallic Mg, and Al-Mg.

[0031] The remainder of the flux-cored wire for gas-shielded arc welding of the present invention is Fe in the steel sheath, iron powder added for adjusting the composition, Fe content in iron alloy powder such as Fe-Si, Fe-Mn, Fe-Ti alloy, and inevitable impurities. Although there are no particular restrictions on the impurities, from the viewpoints of hot cracking and toughness of the weld metal, it is preferable that P is 0.03% or less and S is 0.03% or less.

[0032] Further, the flux filling rate is not particularly limited, but is preferably 8 to 20% of the total mass of the wire from the viewpoint of productivity. EXAMPLES

[0033] The effects of the present invention will now be described in more detail with reference to examples.

[0034] First, JIS G3141 SPHC (C: 0.02 mass%, Si: 0.01 mass%, Mn: 0.40 mass%, P: 0.012 mass%, S: 0.010 mass%) was used for the steel sheath, which was formed into a U-shape and filled with flux at a filling rate of 10 to 15% to form it into a C-shape. The seams of the steel sheath were then welded to form a pipe and drawn to produce flux-cored wires with the compositions shown in Table 1. The diameter of the prototype wire was 1.4 mm.

[0035] [Table 1]

[0036] Using the prototype flux-cored wires shown in Table 1, the amount of spatter generation, arc stability, bead appearance and shape, the presence or absence of defects by X-ray transmission testing, and weld metal performance were investigated.

[0037] The amount of spatter generated was determined as a value per unit time (g / min) by measuring the weight of spatter generated during 1 minute of welding using a copper collection box. The spatter measurement was the average value of 5 measurements taken under welding conditions No. T1 shown in Table 2, and a value of 1.5g / min or less was considered good.

[0038] The arc stability was evaluated based on the magnitude of the voltage, measured five times for 10 seconds while measuring the amount of spatter generation. The evaluation is shown in a chart of voltage fluctuation over time in 1, where the threshold is set at ±1V from the average voltage. If the time during which the voltage fluctuation exceeds the threshold is 90% or less in 10 seconds, the arc is deemed stable, and if the time during which the voltage fluctuation exceeds the threshold is more than 10% in 10 seconds, the arc is deemed unstable.

[0039] Bead appearance and shape: The bead shape was judged to be good if there were no undercuts or overlaps that required reworking in the healthy weld bead. The bead appearance was judged to be good if there was no partial disturbance in the waveform and it was uniform.

[0040] Welding workability and weld metal performance were investigated by conducting multi-pass weld metal tests using specimens with a 35° groove and a root gap of 7 mm and backing metal under the construction conditions of condition No. T2 (hereinafter referred to as low heat input) and condition No. T3 (hereinafter referred to as high heat input / high interpass) shown in Table 2. The arc stability during welding and the bead appearance and shape were investigated. After welding was completed, the backing metal was removed and an X-ray test was performed to check for the presence or absence of welding defects. In addition, tensile test pieces (JIS Z2201 A0) and impact test pieces (JIS Z2202 4) were taken from the weld metal to investigate the mechanical properties.

[0041] The strength was evaluated as tensile strength of 490 to 690 MPa, and the toughness was evaluated as Charpy impact tests were performed at 0°C on five pieces each, with an average absorbed energy of 80 J or more and a minimum of 60 J or more being considered good. The results are summarized in Table 3.

[0042] [Table 2]

[0043] [Table 3]

[0044] In Tables 1 and 3, wire symbols W1 to W10 are examples of the present invention, and wire symbols W11 to W22 are comparative examples. Wires W1 to W10, which are examples of the present invention, have appropriate contents of C, Si, Mn, Mo, Cu, Ti, and B in the flux-cored wire, and appropriate amounts of the total F equivalent value of metal fluorides in the flux, the total SiO2 equivalent value of Si oxides, and the total Na2O equivalent value and K2O equivalent value of one or more types of Na oxide and K oxide, so that the amount of spatter generation is small, and under both low heat input and high heat input / high interpass temperature welding conditions, the arc is stable, the bead appearance and shape are good, there are no welding defects, and the average and minimum values ​​of the tensile strength and absorbed energy of the weld metal are good.

[0045] In addition, for wire symbols W2, W5, W6 and W9, which have appropriate amounts of either or both of Al and Mg, the average absorbed energy of the weld metal was 100 J or more under both low heat input and high heat input / high interpass temperature welding conditions, and the results were extremely satisfactory.

[0046] In the comparative example, wire symbol W11 had low tensile strength of the weld metal under welding conditions of high heat input and high interpass temperature because of low C. In addition, the total SiO2 equivalent value of Si oxide was high, so slag inclusion occurred under both low heat input and high heat input and high interpass temperature welding conditions, and the absorbed energy of the weld metal was low.

[0047] Wire symbol W12 has a high C content, so the tensile strength of the weld metal was high and the absorbed energy was low under both low heat input and high heat input / high interpass temperature welding conditions. In addition, the total F-converted value of metal fluorides was high, so the amount of spatter was large and the arc was strong and unstable under both low heat input and high heat input / high interpass temperature welding conditions.

[0048] Wire symbol W13 has a low Si content, so the tensile strength and absorbed energy of the weld metal were low under both low heat input and high heat input / high interpass temperature welding conditions. Also, because the total SiO2 equivalent value of Si oxides was low, the weld bead toe did not conform well under both low heat input and high heat input / high interpass temperature welding conditions, resulting in poor bead appearance and shape.

[0049] Wire symbol W14 has a high Si content, so slag inclusion occurred under both low heat input and high heat input / high interpass temperature welding conditions, the tensile strength of the weld metal was high, and the absorbed energy was low. In addition, the total F-converted value of metal fluorides was low, so there was a large amount of spatter generation, and the arc was unstable under both low heat input and high heat input / high interpass temperature welding conditions.

[0050] Wire symbol W15 has a low Mn content, so the tensile strength and absorbed energy of the weld metal under welding conditions of high heat input and high interpass temperature were low. In addition, the total of the Na2O equivalent value and K2O equivalent value of one or more types of Na oxide and K oxide is low, so the amount of spatter generated is large and the arc is unstable under both welding conditions of low heat input and high heat input and high interpass temperature.

[0051] Wire symbol W16 has a high Mn content, so the tensile strength of the weld metal was high under low heat input welding conditions, and the minimum absorbed energy was low. Also, because it has a high Mn content, slag inclusion occurred under both low heat input and high heat input / high interpass temperature welding conditions.

[0052] Wire symbol W17 has low Mo content, so the tensile strength of the weld metal was low under welding conditions of high heat input and high interpass temperature. Also, because it has low B content, the absorbed energy of the weld metal was low under welding conditions of high heat input and high interpass temperature.

[0053] Wire symbol W18 has a high Mo content, so the tensile strength of the weld metal was high under low heat input welding conditions, and the minimum absorbed energy was low. Also, because it has a high B content, high temperature cracks occurred in the first layer under both low heat input and high heat input / high interpass temperature welding conditions.

[0054] Wire symbol W19 has a low Cu content, so the minimum absorbed energy of the weld metal was low under both low heat input and high heat input / high interpass temperature welding conditions. In addition, the total of Na2O equivalent value and K2O equivalent value of one or more types of Na oxide and K oxide is high, so the amount of spatter is large, and the arc is unstable under both low heat input and high heat input / high interpass temperature welding conditions, resulting in slag inclusion.

[0055] Wire symbol W20 contains a lot of Cu, so hot cracks occurred in the first layer under both low heat input and high heat input / high interpass temperature welding conditions, and the absorbed energy of the weld metal was low.

[0056] Wire symbol W21 has a low Ti content, so the arc was unstable under welding conditions of high heat input and high interpass temperature, and the absorbed energy of the weld metal was low. In addition, because the total of either or both of Al and Mg was high, the amount of spatter and fume was large.

[0057] Wire symbol W22 has a high Ti content, so the absorbed energy of the weld metal was low under both low heat input and high heat input / high interpass temperature welding conditions. In addition, because the total amount of Al and Mg is low, no effect of improving the absorbed energy was obtained.

Claims

1. A flux-cored wire for gas shielded arc welding, which is made by filling a steel sheath with flux, The mass percentage of the total wire mass is the sum of the steel sheath and flux. C: 0.04-0.10%, Si: 0.4 to 1.4%, Mn: 1.7 to less than 2.5%; Mo: 0.6-1.0%, Cu: 0.05-0.5%, Ti: 0.1 to 0.4%, B: 0.0015 to 0.010%; Furthermore, in the flux, the mass percentage relative to the total mass of the wire is: Metal fluorides: 0.005 to 0.10% in total F conversion value, Si oxide: SiO 2 The total conversion value is 0.01 to 0.2%, One or more of Na oxide and K oxide: Na 2 O conversion value and K 2 The total content of O is 0.02 to 0.14%, A flux-cored wire for gas shielded arc welding, the balance of which consists of Fe in a steel sheath, iron powder added for adjusting the composition, Fe in iron alloy powder, and unavoidable impurities.

2. The mass percentage of the total wire mass is the sum of the steel sheath and flux.

2. The flux-cored wire for gas shielded arc welding according to claim 1, further comprising one or both of Al and Mg: 0.25% or less in total.

Citation Information

Patent Citations

  • Mig welding flux cored wire having less welding deformation

    JP1995088688A

  • Welding wire for gas shielded arc welding

    JP2003136281A

  • Welding wire for gas shielded metal-arc welding

    JP2004237361A

  • Steel wire for carbon dioxide gas-shielded arc welding

    JP2005169415A

  • Flux cored wire for gas shielded arc welding

    JP2005279683A